2018
DOI: 10.4103/0022-3859.201418
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of mental disability using Indian Disability Evaluation Assessment Scale among general population in an urban area of Puducherry, India

Abstract: Background:There is paucity of information on epidemiology of mental disability in India.Objective:The objective of this study was to assess mental disability, and to study the association between sociodemographic and comorbid chronic conditions with mental disability.Materials and Methods:This community-based cross-sectional study was conducted among ≥5 years age group in an urban area attached to a Tertiary Care Medical Institute in Puducherry, India. Mental disability was assessed using Indian Disability Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Other studies using rapid assessment of disability toolkit or otherwise, in India or abroad have also reported low level of education attainment in persons with disability. 8,11,13,15,[20][21][22] Marital status…”
Section: Age and Gender Distribution Of Persons With Disabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies using rapid assessment of disability toolkit or otherwise, in India or abroad have also reported low level of education attainment in persons with disability. 8,11,13,15,[20][21][22] Marital status…”
Section: Age and Gender Distribution Of Persons With Disabilitymentioning
confidence: 99%
“…Other studies conducted in India and other countries worldwide also reported the poor level of employment status of persons with disability. 6,15,19,20,[24][25][26][27][28][29][30] Ganesh et al reviewed 32 studies which reveal that occupation plays a major role as a determinant of disability. 26…”
Section: Age and Gender Distribution Of Persons With Disabilitymentioning
confidence: 99%
“…In a research paper published in this issue of the journal, Kumar et al . [ 8 ] report the degree of disability associated with mental health conditions and linkage with other health conditions in the general population. This study was conducted in a small geographical area, which is a key limitation of the findings, especially when the National Mental Health Survey 2015–2016 report is available and provides information on epidemiology, and health systems challenge on mental health in India.…”
mentioning
confidence: 99%
“…underlines that the mental illnesses are often associated with disabilities. [ 8 ] In addition, both mental illnesses and disabilities are health and social challenges. The mental illnesses are among the leading causes of ill health and disability worldwide.…”
mentioning
confidence: 99%
See 1 more Smart Citation